Nin gii nisaa a'aw waawaashkeshii: engaging animal rights theory with Ojibwe and Cree theories of hunting ethics - Persinger, Corinne, author; McShane, Katie, advisor; Shockley, Kenneth, advisor; Schneider, Lindsey, committee member (Colorado State University. Libraries, 2023)
In this thesis, I call on animal ethicists working in Western traditions to reflect on deeply held assumptions, prejudices, and colonial histories that continue to marginalize not only Indigenous hunting practices, but the very theories that defend their ethical justification. Such reflection is necessary for genuine engagement to take place between Western theories and Indigenous theories of hunting ethics. This thesis can be understood as part of a larger project to clear the way for critical conversation between these different traditions. However, the scope of the thesis is limited to a particular Western theory, that is animal rights theory, and a particular version of Indigenous hunting ethics, based in reciprocity and contextualized by the hunting practices of Ojibwe and Cree cultural groups. I argue that animal rights theorists must engage with Indigenous theories of hunting ethics as a matter of moral and epistemic responsibility. This thesis contains three chapters. In the first chapter, I will motivate the claim that the persistent ignorance to Indigenous ethical theories by Western theorists—and animal rights theorists in particular–is a form of epistemic injustice. I argue that engagement with Indigenous theories by animal rights theorists is a necessary step for overcoming this injustice. In the following chapters, I attempt to motivate the theoretical importance of overcoming the injustice. In the second chapter, I offer an account of animal rights theory that emphasizes possible points of overlap with Indigenous theories. In this account, I argue that animal rights theory requires the addition of relational accounts of animal ethics to be tenable. Relational accounts leave open two substantive theoretical questions that I will take up in chapter three: first, whether relational context matters for our negative obligations; and second, the extent to which animals possess agency and power in their relationships with humans. Ojibwe and Cree hunting ethics, based in a theory of reciprocity, also center relational context for determining our obligations to animals. However, these theories respond to these open questions differently than their Western counterparts. I argue that the difference in how these theories respond to these questions illustrates why they come out so differently in their evaluation of the moral character of hunting. Western and Indigenous ethical theories appeal to quite different conceptual frameworks to assess ethical behavior within hunting relationships. Integral ethical concepts like those of taking life, harm, intentionality, and power can be understood differently when a theory of reciprocity is used to define human-animal relations, instead of the relational theories of their Western counterparts. As a result, the kinds of obligations associated with the act of taking life are different on Indigenous theories. I take these different understandings of ethically significant concepts to be at the heart of the disagreement between animal rights theory and Ojibwe and Cree theories of hunting ethics regarding the moral character of hunting. The ignorance of Western theorists to Indigenous conceptual frameworks allows them to downplay the theoretical significance of this disagreement. These theorists have an ethical and epistemic responsibility to address this ignorance.
Keywords: animal rights theory; Indigenous philosophy; hunting ethics; animal ethics